2022
DOI: 10.1021/acsomega.2c03498
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 Acts as an Effective Energy Donor to Enhance Fluorescence of Yellow Emissive Carbon Dots

Abstract: Carbon dots (CDs) are versatile fluorescent nanocrystals with unique optical and structural properties and are commonly used in biosensing, bioimaging, and biomolecule tagging studies. However, fluorescence of CDs is brightest in the wavelength range of 430–530 nm, which overlaps with the autofluorescence range of many eukaryotic cells and makes CDs impractical for in vivo and in vitro imaging studies. Thus, the design of yellow-red emissive CDs with high quantum yield is of importance. In this study, the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The red-emissive water-soluble CdTeS quantum dots were used to interact with yellow-emissive carbon dots (PhDOTs). Carbon dots were synthesized through a general microwave-based method proposed by Ergüder et al 34 Before checking the CdTeS QD–PhDOTs interaction, the interaction between PhDOTs and l -Cys/NAC was checked (Fig. 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The red-emissive water-soluble CdTeS quantum dots were used to interact with yellow-emissive carbon dots (PhDOTs). Carbon dots were synthesized through a general microwave-based method proposed by Ergüder et al 34 Before checking the CdTeS QD–PhDOTs interaction, the interaction between PhDOTs and l -Cys/NAC was checked (Fig. 10).…”
Section: Resultsmentioning
confidence: 99%
“…A traditional microwave-assisted method was applied to synthesize carbon dots from 1,2-phenylenediamine. 34 Briefly, to synthesize carbon dots (PhDOTs), 400 mg o -phenylenediamine (carbon precursor) was dissolved in 20 mL ultrapure water. Then, the homogeneous solution was placed into a kitchen-type microwave oven (SAMSUNG/model no.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Ergüder, et al , have reported a simple, rapid CDs synthesis method via the MW using o -phenylenediamine and urea. 22 Their synthesis was also conducted in a glass vessel but with a reaction time of 20 minutes at 800 MW and resulted in CDs with a yellow emission capable of sensing the chemical aflatoxin B1 in solution. A study by Liu, et al , reports an optimized method for synthesizing CDs with wavelength-tunable emission via MW irradiation through adjustment of the quantity of precursors.…”
Section: Introductionmentioning
confidence: 99%